PERAN GURU DALAM MENINGKATKAN MINAT SISWA PADA PEMBELAJARAN BACA TULIS AL-QUR’AN - Sarumpaet, Saodah Br (Jurnal Al-Fatih, 2024)
The purpose of this research is to determine the role of teachers as educators in enhancing the interest in learning to read and write the Qur'an, to understand the role of teachers as guides in reading and writing the Qur'an, and to identify the inhibiting factors. This study is a qualitative descriptive research, utilizing purposive sampling to select informants, while data collection techniques include observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions, while the validity of the data is ensured using source triangulation techniques. The research results indicate that the role of teachers as educators has been appropriate in the educational process of their students, as they act as initiators, motivators, and facilitators. The role of teachers as guides means that they have helped students who face learning difficulties, and teachers are able to provide solutions to assist students experiencing learning challenges. Additionally, teachers have also patiently improved the reading of the Qur'an. Factors hindering reading and writing the Qur'an include the negative impact of technological advancements on students' learning of the Qur'an, as well as the importance of parental involvement in students' learning.